Reduced fasting time improves comfort and satisfaction of elderly patients undergoing anesthesia for hip fracture - Luiz Eduardo Imbelloni; Illova Anaya Nasiane Pombo; Geraldo Borges de Morais Filho (Brazilian Journal of Anesthesiology, 2015)
Background and objectives: Patient's satisfaction is a standard indicator of care quality. The aim of this study was to evaluate whether a preoperative oral ingestion of 200 mL of a carbohydrate drink can improve comfort and satisfaction with anesthesia in elderly patients with hip fracture. Method: Prospective randomized clinical trial conducted in a Brazilian public hospital, with patients ASA I–III undergoing surgery for hip fracture. The control group (NPO) received nothing by mouth after 9:00 p.m. the night before, while patients in the experimental group (CHO) received 200 mL of a carbohydrate drink 2–4 h before the operation. Patients’ characteristics, subjective perceptions, thirst and hunger and satisfaction were determined in four steps. Mann–Whitney U-test and Fisher exact test were used for comparison of control and experimental groups. A p-value <0.05 was considered significant. Results: A total of 100 patients were included in one of the two regimens of preoperative fasting. Fasting time decreased significantly in the study group. Patients drank 200 mL 2:59 h before surgery and showed no hunger (p < 0.00) and thirst on arrival to OR (p < 0.00), resulting in increased satisfaction with the perioperative anesthesia care (p < 0.00). Conclusions: The satisfaction questionnaire for surgical patient could become a useful tool in assessing the quality of care. In conclusion, CHO significantly reduces preoperative discomfort and increases satisfaction with anesthesia care. Resumo: Justificativa e Objetivos: A satisfação do paciente é indicador padrão da qualidade da assistência prestada. O objetivo deste estudo foi avaliar se a ingestão de 200 mL oral pré-operatória de uma bebida de carboidratos pode melhorar o conforto e a satisfação com a anestesia no paciente idoso com fratura de quadril. Método: Ensaio clínico prospectivo e randomizado realizado em hospital público de saúde brasileiro, pacientes estado físico ASA I-III submetidos à cirurgia de fratura de quadril. O grupo controle (NPO) não recebeu nada pela boca, após as 21 horas da noite anterior, enquanto que os pacientes no grupo experimental (CHO) recebeu 200 mL de uma bebida de carbohidratos de 2 a 4 horas antes da operação. Características dos pacientes, percepções subjetivas, presença de sede e fome e satisfação dos pacientes foi apurado em quatro etapas. Teste de Mann-Whitney U-test e exato de Fisher foram utilizados entre o grupo controle e o grupo experimental. Valor de p < 0,05 foi considerado significativo. Resultados: Um total de 100 pacientes foram incluídos em um dos dois regimes de jejum pré-operatório. Tempo de jejum diminuiu significativamente no grupo de estudo. Pacientes beberam 200 mL 2:59 h antes da cirurgia e não apresentaram fome (p < 0,00) e sede na chegada à SO (p < 0,00), resultando em aumento da satisfação com o cuidado perioperatório anestesia (p < 0,00). Conclusões: O questionário de satisfação do paciente cirúrgico poderia tornar-se um instrumento útil na avaliação da qualidade de atendimento. Em conclusão, CHO reduz significativamente o desconforto pré-operatório e satisfação com os cuidados da anestesia. Keywords: Spinal anesthesia, Fasting, Satisfaction, Palavras-chave: Raquianestesia, Jejum, Satisfação